Pengaruh penanganan ikan tongkol (Auxis thazard) segar yang berbeda terhadap kadar histamin dan mutu organoleptik - Nyoman Rai Wijana; I Gde Suranaya Pandit; Ni Made Darmadi (Fakultas Pertanian, Universitas Warmadewa, 2018)
This study uses an experimental method using a Completely Randomized Design (CRD) with a single factor, namely handling different fish to organoleptic quality histamine levels consisting of several levels of treatment such as: Handling of tuna at room temperature (control), Handling of mackerel tuna with addition of crushed ice 25% bb which produces a temperature of ±180C, Handling of tuna with the addition of people's salt (10% bb), Handling of mackerel tuna with a mixture of 12.5% ice and 5% salt of the people. The results of the study the effect of handling tuna made histamine levels differ greatly real. The amount of histamine at room temperature averaged 47.78 mg/100g, the amount of histamine in the treatment of crushed ice was 1:4 so that the temperature reached ±18°C averaged 11.30 mg/100g, the amount of histamine in the salt treatment of the people (10% bb) average of 31.00 mg/100g and the amount of histamine in the treatment of 50% mixed treatment B and 50% treatment C averaged 21.45 mg/100g. The effect of handling mackerel tuna makes organoleptic quality that is very significantly different based on appearance. The best appearance in the treatment of crushed ice is 1:4 so that it reaches a temperature of ±18°C of 8.00 with brilliant specifications rather reddish, strong scales, thin mucus. The effect of ear tuna handling results in very different organoleptic qualities based on the eye. The best eye condition in the treatment of 1:4 ice destruction so that the temperature reaches ±18°C at 7.722 with convex specifications, the cornea is somewhat foggy, the pupil is rather dim. The effect of handling mackerel tuna makes organoleptic quality very different based on texture. The texture conditions are best at 1:4 crushed ice treatment so that the temperature reaches ±18°C at 7.83 with elastic specifications. The effect of the handling of tuna produces different organoleptic qualities that are very real based on odor. The analysis showed that the smell was the best in the treatment of 1:4 crushed ice so that the temperature reached ±18°C at 7.778 with the specification of a soft fishy odor. Handling of mackerel tuna should use 1:4 crushed ice to reach a temperature of ±180C because it can maintain histamine levels and organoleptic quality of the fish as a whole.